Randomized resonant metamaterials for single-sensor identification of elastic vibrations - Tianxi Jiang (Nature Portfolio, 2020)
Designing efficient and flexible metamaterial with uncorrelated transmissions for spatial vibration encoding and identification remains a challenge. Here, the authors propose a randomized resonant metamaterial with randomly coupled local resonators for single-sensor identification of elastic vibrations.